El conflicto en Ucrania: el primer enfrentamiento serio de Rusia con Occidente durante la etapa de la Post-Guerra Fría - Sánchez Ramírez, Pablo Telman (El Colegio de México A.C., 2016)
Ukraine has become an unstable region plagued by conflict and nationalist resentment, initially encouraged from outside its borders In October 2013, Ukraine became a priority for Russian foreign policy and the basis for a serious diplomatic, commercial and economic confrontation with the United States and Europe. It is highly likely that as a result of its strategy in Ukraine, the West will achieve precisely the opposite of what it intended with regard to Russia: a strengthening of the latter’s leadership on the regional and global stage; a new escalation of military rearmament, especially in strategic aviation and aerospace defense; and that Russian nationalism will acquire more weight and influence at a national and regional level.